PROFILE OF AMINO ACIDS OF FOREST HONEYS FROM MALLAWA SOUTH SULAWESI - Mahdalia Mahmud; Alfian Noor; Ahyar Ahmad (Marina Chimica Acta, 2018)
Mallawa is one of the areas that has production forests as the second largest honey producer in Maros. The aim of this research determined the profile of amino acids in honey.  Amino acids of two forest honeys were analyzed using ultra performance liquid chromatography (UPLC). The main amino acids detected honeys were glutamic acid (1060.66 mg/kg, 928.85 mg/kg), histidine (700.37 mg/kg, 478.02 mg/kg), and arginin (683.11 mg/kg, 665.08 mg/kg), but tyrosine and serine not detected. Some other amino acids, including threonine, leucine, valine, phenylalanine and proline, displayed similar  values contents of 239.36 mg/kg, 268.15 mg/kg; 225.81 mg/kg, 293.44 mg/kg; 170.12 mg/kg, 226.03 mg/kg; 174.74 mg/kg, 288.11 mg/kg; and 161.58 mg/kg, 257.44 mg/kg, respectively.